The Benifits of Artificial Intelligence in Increasing Students' Interest in Learning ‎ITSKs Muhammadiah Selong Digital Business Innovation - Abdul Majid, Muhip (Sumber Belajar Sejahtera, 2025)
The use of Artificial Intelligence (AI) in Digital Business Innovation student learning is an increasingly relevant issue in the context of digital education. This Journal Article outlines the core issues by explaining the challenges and benefits of AI in education. The purpose of this journal article is to provide a comprehensive understanding of the role of AI in improving digital business innovation student learning in Indonesia. The research method used is a literature review, which includes an analysis of various sources and perspectives related to the use of AI in higher education. The data used in this article includes information from various literature sources, including research findings, scientific articles, and news related to the implementation of AI in education. Examples of AI applications, such as chatbots for academic guidance, online learning systems, and automated assessments, are obtained from these sources. The results of the data analysis indicate that the use of AI in improving learning motivation for Digital Business Innovation students has significant potential to improve the quality of learning. However, attention must be paid to ethical challenges, the risk of dependency, and the important role of human interaction. Solutions such as AI ethics education, strict multi-party regulation, and the integration of AI with human interaction are integral to the conclusions drawn in this journal article.